Art and the expression of indigenous identity. From "Angry sámi" to "Happy sámi" - Baik, Yeonwoo (UiT Norges arktiske universitet, 2017)
Thesis Abstract: This thesis explores the theme "Sámi art", questioning how we can define the concept Sámi art in the contemporary society and how the way Sámi artists express their ethnic identity through their art has changed over time. The thesis is written based on the fieldwork that was conducted in northern Norway area during the spring and the summer in 2016. It follows seven artists of Sámi ethnic origin across different age groups and art fields, and involves observation and semi-structured interviews. The research reveals Sámi artists of different age groups differ in the way they perceive their ethnic identity and how they attempt to reflect it in their art. Younger artists tend to be more open in dealing with their relationship with the Norwegian society and in incorporating new elements from different cultures in their art practices even when they are trying to express their Sámi ethnic identity through their art. However, it does not mean that the word "Sámi art" or "Sámi artist" loses its meaning. As long as Sámi artists are producing the art that can only be created by those who are living this world as Sámi, like they do now, the discussion on Sámi art will be valid. Film Title: Move Like an Artist / Film Synopsis: This film is a record of the art practices and words from seven Sámi artists across different age groups and art fields, filmed during the spring and the summer of 2016 in northern Norway. We will hear them talk about what it is like to be Sámi in the contemporary society, what it is like to be Sámi artists in the globalised world where so many cultures collide with and bind to each other.